Effect of Artemisia vulgaris Extract on Granzyme Expression and Tumor Mass Diameter (Study of Adriamycin Cyclophosphamide Chemotherapy in Adenocarcinoma Mammae C3H Mice Model) - Hardanto, Gery Rifano; Budijitno, Selamat; Hardian, Hardian (Fakultas Kedokteran Universitas Brawijaya, 2021)
Breast cancer incident continues to increase globally. The surgical management can be combined with other therapeutic modalities, including chemotherapy, radiation, and immunotherapy, such as Artemisia vulgaris (AV). This study aimed to determine the effect of AV extract on Granzyme expression and tumor mass diameter growth of C3H mice with adenocarcinoma mammae. Twenty-four female C3H mice were randomly divided into groups of K (control), P1 (AC chemotherapy), P2 (AV extract), and P3 (combination). Adenocarcinoma mammae were inoculated from donor mice. Two cycles of chemotherapy by Adriamycin 0.18 mg and Cyclophosphamide 1.8 mg were given intravenously, while Artemisia vulgaris 13 mg (0.2 ml) was given orally once per day. Granzyme expression was assessed using immunohistochemical staining, while tumor mass diameter growth was measured using tumor calipers. There was a significant negative correlation between and tumor mass diameter growth (p=0,001 and r=-0,911). Artemisia vulgaris increases the apoptotic effects of Adriamycin-Cyclophosphamide chemotherapy by increasing Granzyme expression and decreasing tumor mass diameter growth in adenocarcinoma mammae C3H mice.